Interpreting Granitic Fabrics in Terms of Rhyolitic Melt Segregation, Accumulation, and Escape Via Tectonic Filter Pressing in the Huemul Pluton, Chile. Issue 10 (23rd October 2018) - Garibaldi, Nicolas; Tikoff, Basil; Schaen, Allen J.; Singer, Brad S.
Abstract: The physical process of rhyolite segregation from crystal mushes remains elusive as microstructural evidence of conventional segregation mechanisms is not available. This study provides direct fabric evidence for deformation‐assisted segregation of eruptible rhyolite in the Chilean Andean arc. The shallow (<7 km), 6.4–6.2 Ma Huemul pluton comprises domains of quartz monzonite, granite, and high‐silica granite . Compositional modeling shows that rhyolitic melt ( high‐silica granite ) was extracted from a granitic parent, leaving behind silicic cumulates ( quartz monzonite ). To understand mechanisms of rhyolite segregation, we investigate magmatic fabrics in the pluton. Anisotropy of Magnetic Susceptibility analyses reveal oblate magnetic fabrics and NNW‐striking, subvertical magnetic foliations throughout Huemul. Within the high‐silica granite, magnetic lineations are subvertical and parallel to elongate miarolitic cavities. Magnetic lineations in the quartz monzonite plunge moderately to the NNW, away from the high‐silica granite . In the quartz monzonite, the Shape‐Preferred Orientation of early feldspars is parallel to the magnetic lineation and developed while suspended in melt. Estimations of early feldspar clustering and crystallinity yield 38% of interstitial volume loss in the quartz monzonite and no volume loss in the granite . These fabric data suggest ENE tectonic shortening coeval with rhyolite extraction. We explain these observations with a model of tectonic filter pressing in which shortening is accommodated by interstitial melt flow at slow (10 −5 km 3 /yr) rates, segregating moderate volumes of rhyolite in Myr time scales. These interactions link plutonism, tectonic deformation, and upward mobility of eruptible rhyolite in tectonically active margins. Key Points: Granitic fabrics in a silicic pluton show rhyolite segregation, accumulation, and extraction coeval with tectonic shortening We interpret that a portion of tectonic shortening is accommodated by displaced interstitial melt, that is, tectonic filter pressing Tectonic filter pressing may be the key connecting segregation of rhyolite in volcanic and tectonic time scales in active arcs